Decentralized nonlinear control for power systems using normal forms and detailed models - Singh,AK; Pal,BC (IEEE Transactions on Power Systems, 2017)
This paper proposes a decentralized method fornonlinear control of oscillatory dynamics in power systems. Themethod is applicable for ensuring both transient stability as wellas small-signal stability. The method uses an optimal control lawwhich has been derived in the general framework of nonlinearcontrol using normal forms. The model used to derive the controllaw is the detailed subtransient model of synchronous machinesas recommended by IEEE. Minimal approximations have beenmade in either the derivation or the application of the controllaw. The developed method also requires the application ofdynamic state estimation technique. As the employed control andestimation schemes only need local measurements, the methodremains completely decentralized. The method has been demon-strated as an effective tool to prevent blackouts by simulating amajor disturbance in a benchmark power system model and itssubsequent control using the proposed method.